Stabilizing behaviors of Pseudomonas putida and Pseudomonas alcaligenes bacteria on heavy metal ions in electrolytic manganese residue - Hongliang Chen; Xiangqian Li; Yingxian Zhao; Yutao Zhang (Ecotoxicology and Environmental Safety)
Electrolytic manganese residue (EMR) contains a significant amount of Mn ions as well as Zn, Cu and Cd ions, which have negative environmental impacts due to their toxicity. This study aims to investigate the effects of Pseudomonas putida (P. putida) and Pseudomonas alcaligenes (P. alcaligenes) on the stabilization of heavy metal ions in both simulated solutions and the EMR. The results demonstrated that the synergy of P. putida and P. alcaligenes was more effective than either P. putida or P. alcaligenes alone in stabilizing Mn ions. However, the presence of higher concentration of Zn, Cu and Cd ions in the simulated solution weakened the stabilization effect of Mn ions. Fortunately, when P. putida and P. alcaligenes were synergized together, they exhibited a stronger performance in stabilizing heavy metal ions present in the EMR compared to the bacteria employed alone. After 12 days of fermentation in the EMR slurry, almost all Mn ions were eliminated through the formation of deposits, while the concentrations of Zn, Cu and Cd ions decreased to 0.28 mg/L, 0.2 mg/L and 0.1 mg/L respectively after 10 days fermentation. Under the synergy of P. putida and P. alcaligenes, soluble components such as MnSO4·H2O, (NH4)2Mn(SO4)2·6 H2O and Zn, Cu and Cd compounds from the EMR were transformed into insoluble compounds including (MnCO3, Mn3(PO4)2·3 H2O, Mn2Zn(PO4)2·4 H2O, MnFe2(PO4)2(OH)2·8 H2O), Cu5Zn(PO4)2(OH)6·H2O and Cd(OH)2) for the stabilization of heavy metals ions in the EMR. This study proposes an eco-friendly and low-cost method for rendering EMR harmless through pretreatment.